QTL mapping and candidate gene identification in rice using a Kalarata-Azucena population under salt stress - Ocampo, Marjorie P. de; The, Ho Viet; Thomson, Michael J.; Mitsuya, Shiro; Yamauchi, Akira; Ismail, Abdelbagi M. (Research Square Platform LLC, 2020)
alt stress is a major constraint across large rice production areas in Asia, because of the high sensitivity of modern rice varieties. To identify quantitative trait loci (QTL) associated with salt tolerance in rice, we developed an F2 population from a cross between the salt-tolerant landrace, Kalarata, and the salt-sensitive parent, Azucena. An F2 population was used for DNA extraction, and F2:3 families from this population were screened in a phytotron in a saline nutrient solution at the seedling stage.ResultsAfter 2 weeks at an EC of 12 dS m− 1, the F2:3 families were scored for salt tolerance using IRRI’s Standard evaluation system (SES). Growth, biomass, Na+ and K+ concentrations in leaf tissues, and chlorophyll concentration were determined. A genetic linkage map was constructed with 151 SSRs and InDel markers, which cover 1463 cM with an average distance of 9.69 cM between loci. A total of 13 QTL were identified using Composite Interval Mapping for 16 traits. The short arm of chromosome 1 had the highest density of QTL associated with salt tolerance, which coincides with the Saltol locus; emphasizing the importance of this locus for candidate gene discovery and for use in rice breeding. Several novel QTL were identified on other chromosomes.ConclusionsThe novel QTL identified in this study constitute future targets for molecular breeding, to combine them with other QTLs identified before, for higher and stable performance of rice varieties in salt affected soils. Candidate genes for the large effect QTL on chromosome 3 were found to be involved in diverse biological processes, cellular components, and molecular functions. Several candidate genes in this locus were functionally associated with salt stress tolerance and should further be considered for genetic improvement of rice varieties.